Multi-Layered Films Containing a Biomimetic Stimuli-Responsive Recombinant Protein - Testera AM; Alonso M; Rodríguez-Cabello JC; Barbosa JS; Costa RR; Mano JF (Nanoscale Research Letters, 2009)
Abstract Electrostatic self-assembly was used to fabricate new smart multi-layer coatings, using a recombinant elastin-like polymer (ELP) and chitosan as the counterion macromolecule. The ELP was bioproduced, purified and its purity and expected molecular weight were assessed. Aggregate size measurements, obtained by light scattering of dissolved ELP, were performed as a function of temperature and pH to assess the smart properties of the polymer. The build-up of multi-layered films containing ELP and chitosan, using a layer-by-layer methodology, was followed by quartz-crystal microbalance with dissipation monitoring. Atomic force microscopy analysis permitted to demonstrate that the topography of the multi-layered films could respond to temperature. This work opens new possibilities for the use of ELPs in the fabrication of biodegradable smart coatings and films, offering new platforms in biotechnology and in the biomedical area.